Enantiospecific synthesis of sex pheromone of the obscure mealybug from pantolactone via tandem conjugate addition/cyclization - Hajare, Atul K.; Datrange, Laxmikant S.; Vyas, Samir; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2010)
An efficient synthesis of an enantiomer of insect's natural pheromone is reported starting from chiral pool D-(-)-pantolactone. Highly stereoselective tandem conjugate addition/cyclization sequence and hydrogenation of exocyclic double bond are the key steps in the present synthesis. (C) 2010 Elsevier Ltd. All rights reserved.

Enantiospecific route to (+)-(1R, 3S)-cis-chrysanthemic acid from (-)-D-pantolactone(1) - Hajare, Atul K.; Datrange, Laxmikant S.; Murthy, Y. L. N.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
In this paper, a novel route for the synthesis of (+)-(1R,3S)-cis-chrysanthemic acid is described. The use of readily available (-)-D-pantolactone as a starting point, application of ring-closing metathesis to form the cyclopentene intermediate, and Haller-Bauer/Grob-type fragmentation to form the target compound are the highlights of the present synthesis.
Keywords: alkenes; Metathesis; ring closure; stereoselective synthesis; Wittig reaction

Novel pyrazole-3-carboxamide derivatives as cannabinoid-1 (CB1) antagonists: journey from non-polar to polar amides - Sasmal, Pradip K.; Reddy, D. Srinivasa; Talwar, Rashmi; Venkatesham, B.; Balasubrahmanyam, D.; Kannan, M.; Srinivas, P.; Kumar, K. Shiva; Devi, B. Neelima; Jadhav, Vikram P.; Khan, Sanjoy K.; Mohan, Priya; et al. (Bioorganic & Medicinal Chemistry Letters, 2011)
The synthesis and biological evaluation of novel pyrazole-3-carboxamide derivatives as CB1 antagonists are described. As a part of eastern amide SAR, various chemically diverse motifs were introduced. In general, a range of modifications were well tolerated. Several molecules with high polar surface area were also indentified as potent CB1 receptor antagonists. The in vivo proof of principle for weight loss is exemplified with a lead compound from this series. (C) 2010 Elsevier Ltd. All rights reserved.

Phosphine-mediated synthesis of 1,4-oxazepine- and 1,5-oxazocine-based sugar hybrids from deoxysugar azides - Kurhade, Suresh E.; Salunkhe, Videsh T.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2011)
An efficient and convenient method was developed for the synthesis of novel 1,4-oxazepine- and 1,5-oxazocine-based sugar hybrids from readily available deoxysugar azides by means of tributylphosphine-mediated tandem reactions. The resulting glycoconjugates might be useful in increasing the diversity of sugar backbones, and could find applications as potential glycomimetics and in drug discovery.
Keywords: Alkynes; azides; carbohydrates; heterocycles; oxazepines; oxazocines; Tandem reactions

Synthesis of molluscicidal agent cyanolide a macrolactone from D-(-)-pantolactone - Hajare, Atul K.; Ravikumar, Velayutham; Khaleel, Shaik; Bhuniya, Debnath; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2011)
An efficient synthesis of potent molluscicidal agent cyanolide A, a glycosidic 16-membered macrolide, starting from D-(-)-pantolactone is reported. Highly stereoselective aldol, oxa-Michael addition, and Yamaguchi macrolactonization are the key steps in the present synthesis.

Synthesis of novel dihydrooxazine and oxazoline based sugar hybrids from sugar azides - Kurhade, Suresh E.; Ravula, Sudhir; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2011)
A convenient one-step method for the synthesis of novel dihydrooxazine and oxazoline based sugar hybrids is reported starting from the readily accessible sugar azides and aldehydes. We have used Aube's protocol to achieve this transformation. The resulting glycoconjugates could be used to increase the diversity on the sugar backbone and may find applications as potential glycomimetics and in drug discovery. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dihydrooxazine; Glycoconjugate; Hydroxy azide; Oxazoline; Sugar azide; Sugar hybrids

Total synthesis of isofregenedadiol - Kurhade, Suresh E.; Sanchawala, Abbas I.; Ravikumar, Velayutham; Bhuniya, Debnath; Reddy, D. Srinivasa (Organic Letters, 2011)
The first total synthesis of isofregenedadiol, a bicyclic diterpene isolated from H. Viscosum, is reported starting from a D-(-)-pantolactone chiral pool. A one-pot quadruple reaction sequence comprising an enyne ring-closing metathesis/cross-metathesis/Diels-Alder/aromatization for the construction of a target skeleton Is the highlight of the present synthesis.

Synthesis of a sex pheromone of the longtailed mealybug, pseudococcus longispinus - Kurhade, Suresh E.; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Synthesis-Stuttgart, 2013)
The synthesis of a recently identified and highly active sex pheromone of the longtailed mealybug, Pseudococcus longispinus is reported. A concise synthetic route, use of the under explored Meyer-Schuster rearrangement, Claisen rearrangement, and ring-closing metathesis are the highlights of this work.
Keywords: Acylation; Metathesis; pheromones; rearrangement; Total synthesis